Pemanfaatan Limbah Tongkol Jagung Sebagai Media Budidaya Jamur Merang di Desa Tobadak, Mamuju Tengah - Ganies Riza Aristya; Afifah, Nasywa Kamila; Christophorus Ardhito Haryo Dwinanda; Muhammad Mufid Al-Dayyan; Dita Yulistiani; Elva Maulida Khozana; Rispaini Nur Aziza; Almira Syafataya; Nasywa Kamila Afifah (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Corn is one of the main agricultural products in Tobadak Village. The people in Tobadak Village mainly use the corn kernels to feed their farm animals and then burn or throw away the cob which can be a problem to the environment, especially its soil and air around it. If we can correctly utilise and process its cob, it can be useful to the environment and reduce the pollution around it. One of the products that we can make using this corn cob is straw mushroom cultivation. It does not take long to cultivate this straw mushroom. It takes around 2 weeks to harvest and after that, we can enjoy the benefits. This activity consists of several methods, which are counselling, hands-on practice, society mentoring, monitoring and evaluation. This activity aims to reduce the agricultural waste and improve their knowledge and skill in processing this agricultural waste, especially corn cob to make and cultivate straw mushrooms.